Chondrocalcinosis (Pseudogout) of the Temporomandibular Joint - P. Tvrdý; R. Pink; T. Tichý; P. Heinz; P. Michl (Czech Dental Chamber, 2013)
Introduction: Crystal-induced arthropathies are a frequent inflammatory joint disease. These diseases are characterized by the formation of crystal deposits in joint tissues or in periarticular structures. Calcium pyrophosphate crystal deposition in the temporomandibular joint occurs very rarely. Aim: The aim of this case report is to demonstrate the occurrence of the rare crystal arthropathy in temporomandibular joint, examination methods and therapeutic options.Material and method, results: In this report, we present the case of a 77-year-old woman with chondrocalcinosis of right temporomandibular joint. She underwent removal of pseudotumor after MRI examination. Evaluation of the specimen revealed the presence of rhomboid positively birefringent crystals. Conclusion: It is not easy to make an accurate diagnosis of the disease due to the heterogeneity in the clinical symptoms. Frequently, it imitates various tumours or inflammatory conditions. Histopathological examination with a polarizing microscope and CT and MRI scans are the mainstays of the diagnostics. The principal therapeutic method is the surgical removal of the depositions of crystals.